Antonio Gramsci no centro e na periferia: notas sobre hegemonia e subalternidade - Mussi, Daniela; Goés, Camila (International Gramsci Journal, 2023)
This contribution reconstructs how Antonio Gramsci’s thought “landed” at the centre and at the periphery of the English-speaking world, here Britain and India respectively. With this in mind, it investigates the reception of Gramscian ideas by British and Indian intellectuals, in particular on the basis of the writings of Raymond Williams and Ranajit Guha. The article shows how a free reading of the Prison Notebooks by these intellectuals gave rise to new concepts of Gramscian inspiration, starting especially from the dialectical unity formed by the conceptual coupling hegemonic/subaltern. It sheds light on the originality of the reception of Gramsci’s ideas in these two national contexts in the second half of the twentieth century. With this aim, it first of all reconstructs the political and intellectual environments in which Gramscian ideas were received in Britain and in India, and thence explores the concepts of hegemony and subalternity developed in each of these two contexts. Finally, it presents arguments that aid the integrated and organic understanding of these two contexts of the reception of Gramsci’s ideas, starting from the complex centre-peripheral relationship, as the point of departure for a possible investigation of the reception and international expansion of Gramsci’s thought.